Behavioral Plasticity of Audiovisual Perception: Rapid Recalibration of Temporal Sensitivity but Not Perceptual Binding Following Adult-Onset Hearing Loss - Schormans, Ashley L.; Allman, Brian L. (Frontiers in Behavioral Neuroscience, 2018)
The ability to accurately integrate or bind stimuli from more than one sensory modality is highly dependent on the features of the stimuli, such as their intensity and relative timing. Previous studies have demonstrated that the ability to perceptually bind stimuli is impaired in various clinical conditions such as autism, dyslexia, schizophrenia, as well as aging. However, it remains unknown if adult-onset hearing loss, separate from aging, influences audiovisual temporal acuity. In the present study, rats were trained using appetitive operant conditioning to perform an audiovisual temporal order judgment (TOJ) task or synchrony judgment (SJ) task in order to investigate the nature and extent that audiovisual temporal acuity is affected by adult-onset hearing loss, with a specific focus on the time-course of perceptual changes following loud noise exposure. In our first series of experiments, we found that audiovisual temporal acuity in normal-hearing rats was influenced by sound intensity, such that when a quieter sound was presented, the rats were biased to perceive the audiovisual stimuli as asynchronous (SJ task), or as though the visual stimulus was presented first (TOJ task). Psychophysical testing demonstrated that noise-induced hearing loss did not alter the rats’ temporal sensitivity 2-3 weeks post-noise exposure, despite rats showing an initial difficulty in differentiating the temporal order of audiovisual stimuli. Furthermore, consistent with normal-hearing rats, the timing at which the stimuli were perceived as simultaneous (i.e., the point of subjective simultaneity; PSS) remained sensitive to sound intensity following hearing loss. Contrary to the TOJ task, hearing loss resulted in persistent impairments in asynchrony detection during the SJ task, such that a greater proportion of trials were now perceived as synchronous. Moreover, psychophysical testing found that noise-exposed rats had altered audiovisual synchrony perception, consistent with impaired audiovisual perceptual binding (e.g., an increase in the temporal window of integration on the right side of simultaneity; right TBW). Ultimately, our collective results show for the first time that adult-onset hearing loss leads to behavioral plasticity of audiovisual perception, characterized by a rapid recalibration of temporal sensitivity but a persistent impairment in the perceptual binding of audiovisual stimuli.